The Contribution of Continuing Education in the (Re)construction of Teacher Knowledge - Moro, Valderesa (2022)
Continuing teacher education has been the scene of many discussions in the Brazilian context. However, when it is related to the construction and reconstruction of teachers' knowledge, it is necessary to think about deepening its importance in the sense of the personal and professional constitution of teachers. The motivating question of this study refers to how teaching knowledge is presented in the context of continuing education in Brazilian studies existing in the scope of theses and dissertations found in the repository of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - CAPES (Coordination for the Improvement of Higher Education Personnel) with a time delimitation of 2017-2020. The methodology is qualitative with a descriptive bibliographic approach. From a total of three theses and nine dissertations analyzed, five of them explicitly refer that continuing education contributed to the construction and reconstruction of teaching knowledge.